Teachers expectation of students’ thinking processes in written works: A survey of teachers’ readiness in making thinking visible - As’ari, Abdur Rahman; Kurniati, Dian; Subanji (Journal on Mathematics Education, 2019)
The trends of teaching mathematical thinking and the existence of two thinking skills (critical dan creative thinking) the required by 21st-century skills have created needs for teachers to know their students’ thinking processes. This study is intended to portray how mathematics teachers expect their students showing their thinking processes in students’ written work. The authors surveyed Whatsapp and Telegram group of mathematics teachers. First, the authors shared the result of the literature review and the governmental regulations about the need to develop thinking skills. Second, the authors stated that the potentials of students’ written works as a tool for knowing students’ thinking processes. Third, the authors sent a simple mathematical problem with the topic of algebra and asked the mathematics teachers how should their students answer that problem such that they can easily monitor and assess their students’ thinking processes. A total of 25 teachers participated voluntarily in this survey. Results of the survey were triangulated with direct trial data in lecture classes at both undergraduate and postgraduate levels. The result indicates that participating mathematics teachers do not expect too much for their students to show their thinking processes in written work. Teacher’s focus is mostly on the accuracy and the correctness of their students’ mathematics answer.